Engineering System Resilience to Global Risks: A Resilience Engineering Approach in Modern Infrastructure - Eric Krisna (Archipel: Journal of Indonesian Interdisciplinary Studies, 2026)
The increasing exposure of modern infrastructure systems to global risks such as climate change, multi-hazard disasters, cyber disruptions, and pandemics has highlighted the need for a shift from reliability-based to resilience-based engineering approaches. This study aims to analyze the role of resilience engineering in enhancing the robustness, adaptability, and recovery capabilities of engineering systems under uncertain and complex conditions. The research adopts a qualitative approach using a systematic literature review (SLR) method, with data collected from reputable international journals published between 2021 and 2025. The analysis employs thematic and comparative synthesis to identify key dimensions of resilience, including absorptive, adaptive, and recovery capacities, as well as their integration with risk management frameworks. The findings reveal that resilience engineering significantly improves system performance by enabling infrastructure to anticipate, absorb, and recover from disruptions, while maintaining critical functionality. However, challenges such as multi-hazard modeling, cascading failures, and the lack of standardized resilience metrics remain critical issues. The study concludes that a holistic and integrative approach, combining technical, socio-economic, and environmental dimensions, is essential to develop resilient infrastructure systems capable of addressing global risks and ensuring sustainable performance